2013
DOI: 10.1007/s00198-013-2575-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of osteonecrosis in patients taking bisphosphonates for prevention of osteoporosis: a systematic review and meta-analysis

Abstract: The available evidence suggests that use of BPs in cancer patients is associated with a substantial risk for ONJ. Patients receiving IV BP are at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
1
30
1
1
Order By: Relevance
“…9 In the UK there is a move towards adopting 20 per cent risk for any osteoporotic fracture and 5 per cent for hip fracture. Fixed treatment thresholds for people in the UK are attractive as they are easy to use and allow clear division into low risk (less than 10 per cent for any fracture and 3 per cent for hip fracture), intermediate risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) per cent for any fracture and 3-5 per cent for hip fracture) and high risk (>20 per cent for any and >5 per cent for hip fracture). In the absence of national guidance, the decision as to which treatment threshold to use needs to be agreed locally.…”
Section: Splmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In the UK there is a move towards adopting 20 per cent risk for any osteoporotic fracture and 5 per cent for hip fracture. Fixed treatment thresholds for people in the UK are attractive as they are easy to use and allow clear division into low risk (less than 10 per cent for any fracture and 3 per cent for hip fracture), intermediate risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) per cent for any fracture and 3-5 per cent for hip fracture) and high risk (>20 per cent for any and >5 per cent for hip fracture). In the absence of national guidance, the decision as to which treatment threshold to use needs to be agreed locally.…”
Section: Splmentioning
confidence: 99%
“…ONJ is defined as exposed and necrotic bone in the maxillofacial region that does not heal within eight weeks (see Figure 2). It is a rare adverse event (less than 1 in 1000 18 ) that has been reported with bisphosphonates (particularly intravenous) and denosumab, but the risk of ONJ is far outweighed by the potential benefit of fracture risk reduction. It is thought that the risk of ONJ can be reduced by patients undergoing any necessary dental treatment before starting these medications.…”
Section: Challenges Of Bone Protective Therapymentioning
confidence: 99%
“…Even if some authors suggested that oral bisphosphonates can cause ONJ in patients with osteoporosis, data are very conflicting to date. In fact, recent meta-analysis indicate BFs use for osteoporosis is associated to ONJ incidence, lower than 1 on 100,000 patients every year of exposure (44). Another adverse event that has been linked to extended treatment with bisphosphonates is the occurrence of atypical diaphyseal subtrochanteric fractures.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Four reviews pooled data across studies in a meta-analysis. 120,[122][123][124] Evidence from these reviews indicates that rates of GI toxicity are similar following treatment with alendronic acid, risedronic acid, oral ibandronic acid and placebo. However, observational data suggest a high level of reporting of a number of conditions in the first month of therapy with alendronic acid or risedronic acid, particularly those affecting the upper GI tract.…”
Section: Atrial Fibrillation Loke Et Almentioning
confidence: 99%
“…Recently, Lee et al 120 undertook a meta-analysis of 12 cohort and case-control studies evaluating oral and i.v.-administered bishphosphonates. An inclusion criterion was that the studies were carried out in non-cancer patients.…”
Section: Van Den Wyngaert Et Almentioning
confidence: 99%